PENGUATAN FUNGSI LEGISLASI DEWAN PERWAKILAN DAERAH DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA (ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NO.92/PPU-X/2012) - Andryan Andryan; Muhammad Solly Lubis; Suhaidi Suhaidi; Faisal Akbar Nasution (Universitas Sumatera Utara, 2015)
ABSTRACT Regional Representative Council (DPD) as a new state agency after the 1945 amendment was originally expected to be able to realize the presence of two rooms representation system (bicameral). As an embodiment of the people, the DPD related to the legislative function as stated in the Constitution, 1945. In carrying out its legislative function, the DPD's involvement is limited to the discussion of Level I. In fact, the 1945 allows DPD follow up on the process that takes place in Level II. The Constitutional Court (MK) has strengthened the legislative function of the DPD some previously reduced by Act No.27 of 2009 on MPR, DPR, DPD and DPRD, and Act No. 12 of 2011 on the Establishment of Laws and Regulations. DPD in the legislative function should be viewed as a whole, starting from the submission process to approve a Bill (the Bill). Implications of the decision of the Constitutional Court on strengthening the legislative function of the Regional Representative Council, that DPD is constitutionally have gained in three aspects: first, the authority of DPD in the proposed bill relating to the area; Second, the authority of the Council, who discussed the bill relating to the area; Third, DPD involvement in the preparation of the National Legislation Program. Strengthening the legislative function should be done by rearranging comprehensively legislative function in the system of government, with the fifth amendment of the 1945 Constitution is to establish a system of checks and balances in the representation of the people in the way that the doctrine of popular sovereignty. Keywords: DPD, Legislation, and System of Representatives